Delayed Effect of the Light Pulse on Phosphorylated ERK1/2 and GSK3β Kinases in the Ventrolateral Suprachiasmatic Nucleus of Rat - Červená, Kateřina; Pačesová, Dominika; Spišská, Veronika; Bendová, Zdeňka (Journal of molecular neuroscience, 2015)
The intrinsic period of circadian clock in the suprachiasmatic nucleus is entrained to a 24-h cycle by external cues, mainly light. Previous studies have shown that light applied at night induces robust phosphorylation of extracellular-signal-regulated kinase that is necessary to process the light pulse into the phase shift of the clock phase. In this study, we show the persistent downregulation of phosphorylated extracellular-signal-regulated kinase and transient downregulation of phosphorylated glycogen synthase kinase-3beta in the ventrolateral part of the suprachiasmatic nucleus to photic stimuli starting at 2 h after the beginning of the light pulse. As both kinases are involved in regulation of circadian clockwork, we hypothesize that these changes may contribute to the phase-shifting effect of light at night.
Keywords: MAP kinasový signální systém; Mitogen-Activated Protein Kinase 1; reakční čas; Reaction Time; zvířata; MAP Kinase Signaling System; Rats; Suprachiasmatic Nucleus; světelná stimulace; Glycogen Synthase Kinase 3; mužské pohlaví; nucleus suprachiasmaticus; Mitogen-Activated Protein Kinase 3; Photic Stimulation; kinasa 3 glykogensynthasy; mitogenem aktivovaná proteinkinasa 1; Rats, Wistar; Circadian Clocks; cirkadiánní hodiny; krysa rodu Rattus; potkani Wistar; Animals; mitogenem aktivovaná proteinkinasa 3; Male